Survival analysis of 8785 malignant lymphoma cases in the oral and nasal cavities in the USA: a cohort study - Feifei Jiang; Ai-Hui Yan (BMJ Open)
Objective To identify the factors associated with the survival of malignant Hodgkin and non-Hodgkin lymphomas in oral and nasal cavities.Study design. Retrospective cohort survival analysis.Methods The Surveillance, Epidemiology and End Results 18 database was used to analyse the factors associated with the 5-year survival rate of malignant lymphomas diagnosed in the oral cavity and pharynx (OCP) and nasal cavity and sinus (NCS) regions from 1988 to 2011 for all patients in the USA. Multivariable Cox regression models were used to calculate the HR of malignant lymphoma death overall and by the site of cancer diagnosis.Results Among the 8785 patients included in the analysis, 4103 (46.7%) were women, 6096 (69.4%) were non-Hispanic (NH) white, 635 (7.2%) were NH black and 1209 (13.8%) were Hispanic patients of all races. We found that a higher 5-year survival rate of malignant lymphoma is associated with: female gender; younger age at diagnosis; NH white race/ethnicity; diagnosis in the oral cavity; receiving surgery/radiation and surgery/radiation, surgery and chemotherapy as the treatment; diagnosis at a localised stage and diagnosis in later calendar years. No association with lymphoma subtype was observed.Conclusion We have identified several demographics and prognosis factors associated with the 5-year survival rate of malignant lymphomas in the OCP and NCS regions. These findings warrant greater public health attention on the prognosis of malignant lymphomas in the OCP and NCS regions among the most vulnerable populations.